The Responsibility of Veterinarians to Address Companion Animal Obesity - Barry S. Kipperman; Alexander J. German (Animals, 2018)
Obesity is a modern-day epidemic in both people and companion animals. A summary of the current research on the causes, risk factors, consequences, and implications of overweight and obesity, and the compliance of small-animal practitioners in recognizing and addressing pet obesity, is provided. Ethical and animal welfare concerns are raised regarding these findings. We argue that a patient advocacy posture compels the veterinary profession to confront this issue more reliably. Evidence is presented to support obesity as a One-Health problem, and discrete and practical recommendations for preventing and addressing companion animal obesity are proposed. The One-Health perspective encourages coordinated action by veterinary healthcare professionals in order to address overweight and obesity in companion animals as a public health concern.